AKTIVITAS DAN PERKEMBANGAN ORKES SIMFONI JAKARTA - , Y. EDHI SUSILO, M.HUM.; , Prof. Dr. H. Timbul Haryono, M.Sc.; , Prof. Dr. Victor Ganap, M.Ed. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This dissertation entitled Aktivitas dan Perkembangan Orkes Simfoni Jakarta, is a research focused on the performance of the Jakarta Symphony Orchestra, as an asset of Jakarta metropolitan city, which was organized and managed by the Jakarta Provincial Government, in cooperation with Radio Republik Indonesia Broadcasting Agency. The symphony orchestra is one of Western classical music groups in the form of an orchestra with a full capacity of instruments, consisted of the strings section, wood wind section, brass section, and percussion section, performed by 60 to 100 musicians. The research aims to highlight the important role played by the Jakarta Symphony Orchestra, its historical background, the activities and development since its establishment in 1970, analysing its prospect of continuities in supporting and enriching the musical life of Jakarta urban society. This is a qualitative research conducted based on musicological science, using a multi disciplines approaches. Research outcome has shown that management of a symphony orchestra that come from the European tradition to all over the world including Indonesia need a professional treatment, due to its high cost of production in managing its rehearsal and performance, apart from the provision of musical instruments, hiring a concert hall, availability of symphony musical scores, and remuneration of the musicians. The existence of Jakarta Symphony Orchestra has not only provided the opportunity for Jakarta audiences to enjoy the symphonic music performance, but has also inspired to the establishment of other symphony orchestras in other cities in Indonesia. In fact, for the past three decades, the Jakarta Symphony Orchestra has produced a lot of concert performances. However, its continuity is in need of a patronage system, in order to be able to manage its organizational activities and for the sake of its musicians welfare. The research is trying to offer a novelty and useful concept of managing the orchestra in strive to achieve an integrated professional level, in terms that the Jakarta Symphony Orchestra is not only professional in its musical performance, but also managed to earn living from time to time.